Why Single-Cell Sequencing Has Promise in MDS - Zhang, Xuan; Grimes, H. Leighton (Frontiers in Oncology, 2021)
Myelodysplastic syndromes (MDS) are a heterogeneous group of diseases characterized by ineffective hematopoiesis. The risk of MDS is associated with aging and accumulation of somatic mutations in hematopoietic stem cells and progenitors (HSPC). While advances in DNA sequencing in the past decade unveiled clonal selection driven by mutations in MDS, it is unclear at which stage the HSPCs are trapped, and what prevents their maturation. Single-cell-sequencing techniques in recent years have revolutionized our understanding of normal hematopoiesis by identifying the transitional cell states between classical hematopoietic hierarchy stages, and most importantly the biological activities behind cell differentiation and lineage commitment. Emerging studies have adapted these powerful tools to investigate the clonal heterogeneity in myeloid malignancies and provide a progressive description of disease pathogenesis. This review summarizes the evolving efforts to elucidate hematopoiesis in MDS and physiological conditions at single cell resolution, the potential of growing single-cell-sequencing techniques and discuss how they may fill the gaps in our current understanding of MDS biology.